Anatomical adaptations of Myriostachya wightiana Hook. F. To salt stress - Rashid, Parveen; Ahmed, Ashfaque (Dhaka University Journal of Biological Sciences, 2011)
Key words: Anatomy; Salt stress; Stem; Leaf; Root; Myriostachya wightiana DOI: http://dx.doi.org/10.3329/dujbs.v20i2.8982 DUJBS 2011; 20(2): 205-208